IMPLEMENTASI PENILAIAN AUTENTIK KURIKULUM 2013 PADA MATA PELAJARAN PAI DAN BUDI PEKERTI - Widi Puspitasari; Hamengkubuwono Hamengkubuwono; Mutia Mutia; Idi Warsah (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: Analysis of Curriculum 2013 authentic asseasement implementation on Islamic education and character subjectsThe present study aimed at finding out a depiction of the implementation of the 2013 curriculum authentic assessment conducted by Islamic education and character teachers in class VII of SMP IT Khoiru Ummah, Rejang Lebonng, Bengkulu. This study used a qualitative approach, and the informants were PAI teacher, curriculum representatives. The data were collected by using observation, interview, and documentation techniques. After collected, the data were further analyzed referring to the concept developed by Miles. et al. with stages comprising data reduction, data presentation, verification and conclusion drawing. The conclusions of this study were as follows: The implementation of 2013 curriculum authentic assessment on Islamic education and character subjects, in terms of the application of attitude assessment, cognitive assessment, and assessment of skills or psychomotor, had been running in accordance with the rules of 2013 curriculum authentic assessment despite not yet running maximally. The supporting factors were such as a safe, comfortable and orderly learning environment, and the availability of facilities and infrastructure at school. The inhibiting factor was that teachers’ less understanding of authentic assessment made them experience difficulties in implementing authentic assessment, besides lack of time in evaluation.